A Novel Solution Approach Based on Dominance Evaluation Measure for Project Scheduling in Multi-Project Environments - Yousefzadeh, Hamid Reza; Tirkolaee, Erfan Babaee; Kiani, Farzad (MDPI, 2024)
The widely recognized measure for resources called resource strength (RS) does not fully capture the resources complexity of a project. Therefore, it cannot be used as a standalone measure to distinguish the complexity of various instances of project scheduling problems. Consequently, additional resource measures such as total amount of overflow (TAO) have been introduced, which should be used in conjunction with the RS. Extensive experimental studies have shown that as the value of TAO increases in a project, scheduling schemes with higher dimensional scheduling schemes such as bi-directional and tri-directional result in schedules with shorter makespans. In this study, an effective approach is proposed for integrating projects in multi-project environments, called the integrated project approach (IPA), taking into account the influence of TAO and building upon the relation between the TAO and the scheduling generation schemes. To assess the performance of IPA, we develop a new random multi-project generator based on the well-known benchmark sets, which utilizes TAO as a control tool to generate instances. The findings indicate that prioritizing the projects and frequency of the projects integration, facilitated by the proposed IPA, have a positive impact on the quality of multi-project schedules.
Keywords: Project Scheduling; Resource Complexity Measure; Multi-Dimensional Scheduling Scheme; Multi-Project Environment; Dominance Evaluation Measure